68Ga-DOTATOC PET/CT in Pleural Solitary Fibrous Tumors. (June 2021) - Lococo, Filippo; Rufini, Vittoria; Filice, Angelina; Paci, Massimiliano; Rindi, Guido
Abstract : Abstract: Solitary fibrous tumor of the pleura (SFTP) is a rare mesenchymal neoplasm. Preoperative diagnosis is usually difficult and based on radiological findings only. We report the imaging results observed in 5 patients with SFTP (2 malignant) obtained by 68 Ga-DOTATOC PET/CT. At qualitative analysis, all tumors showed uptake of 68 Ga-DOTATOC. Mean tumor SUVmax was 9.9 ± 5.7. The expression of SST2 (somatostatin receptors subtype 2) was confirmed by immunohistochemistry in 2 tumor samples, and by gene amplification of SST2 mRNA in all cases. These data suggest a diagnostic role of radioreceptor PET/CT in SFTP, and open novel potential treatment options in unresectable/metastatic disease.